Carbon ceramic material as well as preparation method and application thereof

By using gel slurry to wrap silicon carbide particles during the preparation process of ceramic brake discs, the problem that silicon carbide cannot fill the large pores is solved, and the structural density and mechanical properties of carbon ceramic materials are improved.

CN119797925APending Publication Date: 2025-04-11BYD CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311309790.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the silicon seepage process of existing ceramic brake discs, silicon carbide cannot effectively fill large-sized holes, resulting in a significant reduction in the mechanical properties of the material.

Method used

By immersing the carbon fiber embryo body into a gel slurry containing gel monomer and a crosslinking agent, a gel frame wrapped with silicon carbide particles is formed, large pore sizes are divided, and carbon ceramic material with dense structure is prepared through resin filling, curing treatment, drying and liquid-phase silicon penetration.

Benefits of technology

The prepared carbon ceramic material has a small size, a dense structure, high flexural compressive strength, and significantly improved mechanical strength and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797925A_ABST
    Figure CN119797925A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon ceramic material, the carbon ceramic material comprises a matrix and free silicon dispersed in the matrix, and the matrix comprises carbon fibers and silicon carbide; wherein the size of free silicon in the matrix is 10 [mu] m or less. According to the preparation method provided by the invention, the carbon fiber blank is immersed into the gel slurry containing the gel monomer and the cross-linking agent, the gel skeleton wrapped with the silicon carbide particles is formed through gelation cross-linking, and the large aperture of the carbon fiber blank is divided by the gel skeleton connected with the silicon carbide particles; therefore, the prepared silicon carbide substrate has a small-aperture three-dimensional network porous skeleton structure. And then the silicon carbide matrix is sequentially subjected to resin filling, curing treatment, drying and liquid-phase siliconizing, so that the prepared carbon-ceramic material is small in free silicon size, compact in material structure, good in structural stability and high in bending and compressive strength, and the mechanical strength and the mechanical property are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of carbon ceramic materials, and in particular relates to a carbon ceramic material and a preparation method and application thereof. Background Art

[0002] Most of the ceramic brake discs currently prepared are obtained by siliconizing a C / C blank. Since the C / C blank is stacked by fibers and then obtained through the CVI process, it has a large number of large-sized through-holes. After siliconizing, the silicon carbide generated by the reaction cannot effectively fill such large-sized holes, resulting in a large amount of large-sized free silicon in the prepared ceramic brake disc, which significantly reduces the mechanical properties of the material. Summary of the invention

[0003] The purpose of the present invention is to provide a carbon ceramic material and a preparation method and use thereof. The carbon ceramic material provided by the present invention has small free silicon size, dense structure, high bending and compressive strength, high mechanical strength and good mechanical properties.

[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a carbon ceramic material, wherein the carbon ceramic material comprises a matrix and free silicon dispersed in the matrix, and the matrix comprises carbon fibers and silicon carbide;

[0005] Wherein, the size of free silicon in the substrate is less than 10 μm.

[0006] Optionally, the size of free silicon in the matrix is ​​1-7 μm.

[0007] Optionally, based on the total mass of the matrix, the content of carbon fiber in the matrix is ​​40-60wt%, the content of silicon carbide is 20-50wt%, and the content of free silicon is 1-10wt%.

[0008] Optionally, the density of the carbon ceramic material is 2.0-2.3 g / cm 3 .

[0009] Optionally, the carbon ceramic material has a bending strength of 9 to 14 MPa and a compressive strength of 100 to 160 MPa.

[0010] A second aspect of the present invention provides a method for preparing a carbon ceramic material, wherein the method comprises:

[0011] S1, mixing silicon carbide powder, dispersant, gel monomer, crosslinking agent, initiator and water to obtain gel slurry;

[0012] S2, after mixing the carbon fiber embryo and the gel slurry, performing a first curing treatment and a first drying treatment to obtain a silicon carbide matrix;

[0013] S3, mixing the silicon carbide substrate and the thermosetting resin solution and performing a second drying treatment, and then sequentially performing a second curing treatment, a carbonization treatment and liquid phase siliconization;

[0014] Wherein, the mass ratio of silicon carbide in the gel slurry to the thermosetting resin monomer in the thermosetting resin solution is (1-5):1.

[0015] Optionally, the pore diameter of the silicon carbide substrate is less than 20 μm.

[0016] Optionally, relative to 100 parts by weight of water, the content of silicon carbide powder in the gel slurry is 225 to 400 parts by weight, the content of dispersant is 2 to 4 parts by weight, the content of gel monomer is 10 to 40 parts by weight, the content of cross-linking agent is 1 to 4 parts by weight, and the content of initiator is 0.25 to 1 part by weight.

[0017] Optionally, the mass ratio of the carbon fiber embryo to the silicon carbide powder in the gel slurry is (1.5-3): 1

[0018] Optionally, based on the total mass of the gel slurry, the solid content of the silicon carbide is 45 to 80 wt %.

[0019] Optionally, the thermosetting resin solution comprises a thermosetting resin monomer and an organic solvent, wherein the thermosetting resin monomer is selected from one or more of phenolic resin, epoxy resin and furan resin; and the concentration of the thermosetting resin solution is 5 to 40 wt %.

[0020] Optionally, the dispersant is selected from one or more of ethylene glycol and tetramethylammonium hydroxide;

[0021] The gel monomer is selected from one or more of acrylamide derivatives;

[0022] The cross-linking agent is selected from one or more of methylenebisacrylamide, vinyl chloride and ethylene;

[0023] The initiator is selected from one or more persulfates.

[0024] Optionally, the carbon fiber embryonic body comprises a carbon fiber needle-punched embryonic body;

[0025] The density of the carbon fiber needle punched embryo is 1.0-1.2 g / cm 3 The acupuncture density is 40 to 45 needles / cm 3 .

[0026] Optionally, in step S2, the mixing is performed under reduced pressure conditions, and the reduced pressure conditions include: a processing time of 0.5 to 0.8 h and a relative vacuum degree of 0.095 MPa or more.

[0027] Optionally, in step S2, the conditions of the first curing treatment include: a curing temperature of 60 to 70° C. and a heat preservation time of 3 to 4 hours.

[0028] Optionally, in step S2, the conditions of the first drying treatment include: a drying temperature of 100 to 120° C. and a drying time of 2 to 3 hours.

[0029] Optionally, in step S3, the mixing is performed under reduced pressure conditions, and the reduced pressure conditions include: a processing time of 0.5 to 0.8 h and a relative vacuum degree of 0.095 MPa or more.

[0030] Optionally, in step S3, the conditions of the second drying treatment include: a drying temperature of 60 to 70° C. and a drying time of 8 to 10 hours.

[0031] Optionally, in step S3, the conditions of the second curing treatment include: a curing temperature of 120 to 150° C. and a heat preservation time of 3 to 4 hours.

[0032] Optionally, in step S3, the conditions of the carbonization treatment include: a carbonization temperature of 1000-1200° C. and a holding time of 3-4 hours.

[0033] Optionally, in step S3, the reaction conditions of the liquid phase siliconization include: the silicon source is selected from silicon powder, the heat treatment temperature is 1600-1750° C., and the heat treatment time is 1-2 hours.

[0034] The third aspect of the present invention provides a carbon ceramic material prepared by the method described in the second aspect of the present invention.

[0035] The fourth aspect of the present invention provides use of the carbon ceramic material described in the first aspect and the third aspect of the present invention in a vehicle or an aircraft.

[0036] Through the above technical scheme, the preparation method provided by the present invention is to immerse the carbon fiber embryo into a gel slurry containing a gel monomer and a cross-linking agent, and form a gel skeleton wrapped with silicon carbide particles through gelation and cross-linking. The large pore size of the carbon fiber embryo is divided by the gel skeleton connected with silicon carbide particles, so that the prepared silicon carbide matrix has a three-dimensional network porous skeleton structure with small pores. Then the silicon carbide matrix is ​​sequentially filled with resin, cured, dried and liquid-phase siliconized, so that the free silicon size in the prepared carbon ceramic material is small, the structure is dense, the structural stability is good, the bending and compressive strengths are high, and the mechanical strength and mechanical properties are significantly improved.

[0037] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0039] Figure 1 This is a SEM image of the carbon ceramic material prepared in Example 1 of the present invention.

[0040] Figure 2 This is a SEM image of the carbon ceramic material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0042] A first aspect of the present disclosure provides a carbon ceramic material, wherein the carbon ceramic material comprises a matrix and free silicon dispersed in the matrix, wherein the matrix comprises carbon fibers and silicon carbide;

[0043] The size of the free silicon in the substrate is less than 10 μm, preferably 1 to 7 μm, and more preferably 1 to 3 μm.

[0044] The carbon ceramic material provided by the present disclosure has small-sized free silicon, a dense structure, high bending and compressive strength, high mechanical strength and good mechanical properties. Among them, controlling the size of the free silicon in the carbon ceramic material provided by the present disclosure within a more preferred range can further improve the bending and compressive strength of the material, thereby making the material have higher mechanical strength and better mechanical properties. Among them, in the present disclosure, the free silicon is elemental silicon.

[0045] In a specific embodiment of the present disclosure, based on the mass of the matrix, the content of carbon fiber in the matrix is ​​40-60wt%, preferably 50-60wt%, the content of silicon carbide is 20-50wt%, preferably 30-40wt%, and the content of free silicon is 1-10wt%, preferably 1-5wt%.

[0046] In a specific embodiment of the present disclosure, the density of the carbon ceramic material is 2.0-2.3 g / cm 3 , preferably 2.2 to 2.3 g / cm 3 .

[0047] In a specific embodiment of the present disclosure, the carbon ceramic material has a flexural strength of 9 to 14 MPa, preferably 12 to 14 MPa, and a compressive strength of 100 to 160 MPa, preferably 140 to 160 MPa.

[0048] In the above-mentioned embodiments, when the free silicon content is controlled within a preferred range, the carbon ceramic material provided by the present disclosure can have a denser structure, higher bending and compressive strength, and better mechanical properties.

[0049] A second aspect of the present disclosure provides a method for preparing a carbon ceramic material, wherein the method comprises:

[0050] S1, mixing silicon carbide powder, dispersant, gel monomer, crosslinking agent, initiator and water to obtain gel slurry;

[0051] S2, after mixing the carbon fiber embryo and the gel slurry, performing a first curing treatment and a first drying treatment to obtain a silicon carbide matrix;

[0052] S3, mixing the silicon carbide substrate and the thermosetting resin solution and performing a second drying treatment, and then sequentially performing a second curing treatment, a carbonization treatment and liquid phase siliconization;

[0053] The mass ratio of silicon carbide in the gel slurry to the thermosetting resin monomer in the thermosetting resin solution is (1-5):1, preferably (3-5):1.

[0054] The preparation method provided by the present disclosure is to immerse the carbon fiber embryo into a gel slurry containing a gel monomer and a cross-linking agent, and form a gel skeleton wrapped with silicon carbide particles through gelation and cross-linking. The large pore size of the carbon fiber embryo is divided by the gel skeleton connected with silicon carbide particles, so that the prepared silicon carbide matrix has a three-dimensional network porous skeleton structure with small pores. The silicon carbide matrix is ​​then sequentially filled with resin, cured, dried and liquid-phase siliconized, so that the free silicon size in the prepared carbon ceramic material is small, the structure is dense, the structural stability is good, the bending and compressive strengths are high, and the mechanical strength and mechanical properties are significantly improved.

[0055] In a specific embodiment of the present disclosure, in step S2, the pore diameter of the silicon carbide substrate is less than 20 μm, preferably less than 10 μm.

[0056] In the above embodiment, by preparing a silicon carbide matrix with a three-dimensional network porous skeleton structure having a smaller pore size, the size of free silicon is further reduced, thereby obtaining a carbon ceramic material with excellent mechanical strength and mechanical properties.

[0057] In a specific embodiment of the present disclosure, relative to 100 parts by weight of water, the content of silicon carbide powder in the gel slurry is 225-400 parts by weight, the content of dispersant is 2-4 parts by weight, the content of gel monomer is 10-40 parts by weight, the content of cross-linking agent is 1-4 parts by weight, and the content of initiator is 0.25-1 part by weight. Preferably, the content of silicon carbide powder in the gel slurry is 350-400 parts by weight, the content of dispersant is 2.5-3 parts by weight, the content of gel monomer is 20-30 parts by weight, the content of cross-linking agent is 2-3 parts by weight, and 2-3 parts by weight is 0.5-0.75 parts by weight.

[0058] In the above embodiment, controlling the content of the components in the gel slurry within the specified range of the present invention can make the structure of the gel skeleton connected with silicon carbide particles formed in the gel slurry more stable, so that the prepared silicon carbide matrix has a three-dimensional porous skeleton structure with small pore size, and the free silicon in the prepared carbon ceramic material is small and uniform in size, dense in structure, and has high bending and compressive strength, thereby further improving its mechanical strength and mechanical properties.

[0059] In a specific embodiment of the present disclosure, the mass ratio of the carbon fiber embryo to the silicon carbide powder in the gel slurry is (1.5-3):1, preferably (1.5-2):1.

[0060] In a specific embodiment of the present disclosure, based on the total mass of the gel slurry, the solid content of the silicon carbide is 45 to 80 wt %, preferably 60 to 80 wt %.

[0061] The above preferred solid content of silicon carbide can further adjust the free silicon in the carbon ceramic material to a more preferred size, thereby further improving the mechanical strength of the material.

[0062] In a specific embodiment of the present disclosure, the thermosetting resin solution comprises a thermosetting resin monomer and an organic solvent, wherein the thermosetting resin monomer is selected from one of phenolic resin, epoxy resin and furan resin, preferably phenolic resin; the concentration of the thermosetting resin solution is 5 to 40 wt%, preferably 20 to 30 wt%.

[0063] The concentration of the above-mentioned preferred thermosetting resin solution can further improve the curing effect, allowing the slurry to better enter the interior of the embryo, reducing the porosity of the embryo after drying, further reducing the size of free silicon in the product after subsequent siliconization treatment, and further improving the strength and stability of the material.

[0064] In a specific embodiment of the present disclosure, the dispersant is selected from one or more of ethylene glycol and methylammonium hydroxide, preferably ethylene glycol;

[0065] The gel monomer is selected from one or more acrylamide derivatives, preferably one or more acrylamide and dimethylacrylamide;

[0066] The cross-linking agent is selected from one or more of methylenebisacrylamide, vinyl chloride and ethylene, preferably methylenebisacrylamide;

[0067] The initiator is selected from one or more persulfates, preferably one or more of ammonium persulfate and potassium persulfate.

[0068] In the above embodiment, the types of gel monomers, cross-linking agents, dispersants and initiators are controlled within the scope specified in the present application, and the prepared gel slurry contains covalent bonds, so that the structure of the gel skeleton connected with silicon carbide particles formed in the gel slurry is more stable, so that the prepared silicon carbide matrix has a three-dimensional porous skeleton structure with small pore size.

[0069] In a specific embodiment of the present disclosure, in step S2, the carbon fiber embryo body includes a carbon fiber needle-punched embryo body;

[0070] In a preferred embodiment of the present disclosure, the carbon fiber embryo is selected from a carbon fiber needle-punched embryo, and the density of the carbon fiber needle-punched embryo is 1.0 to 1.2 g / cm 3 , preferably 1.1 to 1.2 g / cm 3 The acupuncture density is 40 to 45 needles / cm 3 , preferably 43 to 45 needles / cm 3 In a specific embodiment of the present disclosure, a preform with a specification size of 200 mm×200 mm×15 mm is selected, and the needle density is adjusted to 40 needles / cm 3 The needling depth is 13 mm, and the carbon fiber needling embryo body in step S2 is obtained.

[0071] In the above embodiment, according to the product to be prepared, the density of the carbon fiber needle-punched embryo and the needle-punching density are controlled within a preferred range, so that a better needle-punching effect and a better embryo structure can be obtained, so that the prepared carbon fiber embryo has higher strength, thereby improving the various mechanical properties of the carbon ceramic material disclosed in the present invention; on the other hand, according to the diameter of the final prepared product, the length of the embryo is preferably the product radius, so that the subsequent siliconization process has a good effect and is easy to operate.

[0072] In a specific embodiment of the present disclosure, in step S2, the mixing is carried out under reduced pressure conditions, and the reduced pressure conditions include: a processing time of 0.5 to 0.8 h, a relative vacuum degree of 0.095 MPa or more, preferably, a processing time of 0.5 to 0.6 h, and a relative vacuum degree of 0.095 to 0.1 MPa.

[0073] In the above embodiment, the preferred mixing treatment time and the relative vacuum degree used for mixing can completely expel the air in the pores of the carbon fiber needle-punched embryo, so that the carbon fiber needle-punched embryo and the gel slurry are in more sufficient and uniform contact, thereby making the silicon carbide matrix structure more dense and stable.

[0074] In a specific embodiment of the present disclosure, in step S2, the conditions of the first curing treatment include: a curing temperature of 60-70°C and a holding time of 3-4 hours. Preferably, the curing temperature is 60-65°C and the holding time is 3-4 hours.

[0075] In the above-mentioned embodiment, the preferred curing treatment conditions can obtain a better curing effect, so that the material forms a stable three-dimensional structure, and further improve the strength and stability of the material.

[0076] In a specific embodiment of the present disclosure, in step S2, the conditions of the first drying treatment include: a drying temperature of 100-120° C., and a drying time of 2-3 hours. Preferably, the drying temperature is 100-110° C., and the drying time is 2.5-3 hours.

[0077] In the above embodiment, the preferred drying treatment conditions can volatilize part of the excess solvent, so that the structure of the formed porous matrix is ​​denser and more stable, and the performance of the material is further improved.

[0078] In a specific embodiment of the present disclosure, in step S3, the mixing is performed under reduced pressure conditions, and the reduced pressure conditions include: a processing time of 0.5 to 0.8 h, a relative vacuum degree of 0.095 MPa or more, preferably, a processing time of 0.5 to 0.6 h, and a relative vacuum degree of 0.095 to 0.1 MPa.

[0079] In the above embodiment, the preferred mixing treatment time and the relative vacuum degree used for mixing can completely expel the air in the pores of the silicon carbide substrate, so that the silicon carbide substrate and the phenolic resin solution are mixed more evenly, further improving the structural stability and mechanical strength of the carbon ceramic material disclosed in the present invention.

[0080] In a specific embodiment of the present disclosure, in step S3, the conditions of the second drying treatment include: a drying temperature of 60-70° C., and a drying time of 8-10 hours. Preferably, the drying temperature is 60-65° C., and the drying time is 9-10 hours.

[0081] In a specific embodiment of the present disclosure, in step S3, the conditions of the second curing treatment include: a curing temperature of 120-150° C. and a holding time of 3-4 hours. Preferably, the curing temperature is 140-150° C. and a holding time of 1-2 hours.

[0082] In the above-mentioned embodiment, the preferred drying and curing conditions of the siliconizing process can achieve a better curing effect, allowing the material to form a stable three-dimensional structure, further improving the strength and stability of the material.

[0083] In a specific embodiment of the present disclosure, in step S3, the conditions of the carbonization treatment include: a carbonization temperature of 1000-1200° C. and a holding time of 3-4 hours. Preferably, the carbonization temperature is 1000-1100° C. and the holding time is 3-3.5 hours.

[0084] In the above embodiment, the preferred carbonization treatment conditions can completely evaporate the excess solvent, making the material structure denser and more stable.

[0085] In a specific embodiment of the present disclosure, in step S3, the reaction conditions of the liquid phase siliconization include: the silicon source is selected from silicon powder, the heat treatment temperature is 1600-1750°C, and the heat treatment time is 1-2h. Preferably, the heat treatment temperature is 1700-1750°C, and the heat treatment time is 1.5-2h.

[0086] In the present disclosure, the various process conditions in the preferred step S3 can further control the residual carbon rate after the phenolic resin is completely pyrolyzed into carbon, avoid the volume expansion of the material, and achieve the advantages of low porosity, small free silicon size, dense structure, and better stability in the prepared material, thereby further improving the performance of the material.

[0087] A third aspect of the present disclosure provides a carbon ceramic material prepared by the method described in the second aspect of the present disclosure.

[0088] A fourth aspect of the present disclosure provides use of the carbon ceramic material described in the first aspect and the third aspect of the present disclosure in a vehicle or an aircraft.

[0089] The carbon ceramic material provided in the present disclosure can be used to prepare carbon ceramic brake discs for use in vehicles or aircraft.

[0090] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0091] Example 1

[0092] a. 600g carbon fiber embryo body uses carbon fiber needle-punched embryo body, and obtains the needle-punched embryo body by unit lamination needle-punching, wherein the density of the needle-punched embryo body is 1.2g / cm 3 The acupuncture density is 42 needles / cm 3 ;

[0093] b. Mix 3 g of ethylene glycol, 400 g of silicon carbide powder, 30 g of acrylamide, 3 g of methylenebisacrylamide, 0.75 g of ammonium persulfate and water to obtain a gel slurry;

[0094] c. Degassing the gel slurry in step b, immersing the acupuncture embryo in step a into the degassing gel slurry, and performing a vacuum treatment for 0.5 h to obtain acupuncture embryo immersed in gel slurry;

[0095] d. Taking out the needle-punched embryo body soaked in gel slurry for curing and drying to obtain a silicon carbide matrix, wherein the curing temperature is 60° C., the curing time is 4 h, the drying temperature is 100° C., the drying time is 2 h, and the solid content of silicon carbide in the gel slurry is 75 wt %;

[0096] e. Mix the silicon carbide substrate in step d with a phenolic resin solution having a concentration of 40 wt %, and perform a vacuum treatment for 0.5 h, and then perform a drying treatment. Place the dried silicon carbide substrate in an oven at 150° C. for curing for 2 h to obtain a cured embryo, wherein the drying temperature is 60° C., the drying time is 9 h, the phenolic resin solution contains 83 g of phenolic resin monomer, and the mass ratio of silicon carbide in the gel slurry to the phenolic resin monomer in the phenolic resin solution is 4.8:1;

[0097] f. placing the solidified embryo in step e in a carbonization furnace for carbonization treatment and removing burrs and processing heat dissipation holes to obtain a carbonized embryo, wherein the carbonization temperature is 1000° C. and the holding time is 3 hours;

[0098] g. Liquid phase siliconizing the carbonized body in step f to obtain a carbon ceramic body, wherein the silicon source is silicon powder, the siliconizing temperature is 1700° C., and the heat treatment time is 2 h;

[0099] h. Mechanically process the disk surface and side surfaces of the carbon ceramic body in step g to obtain a carbon ceramic material.

[0100] Example 2

[0101] The method of Example 1 is adopted, except that in step b, the gel slurry contains 2.4 g of ethylene glycol, 320 g of silicon carbide powder, 24 g of acrylamide, 2.4 g of methylenebisacrylamide, 0.6 g of ammonium persulfate and water; in step d, the solid content of silicon carbide in the gel slurry is 60 wt %;

[0102] In step e, the phenolic resin solution contains 67 g of phenolic resin monomer.

[0103] Example 3

[0104] The method of Example 1 is adopted, except that in step b, the gel slurry contains 1.8 g of ethylene glycol, 240 g of silicon carbide powder, 18 g of acrylamide, 1.8 g of methylenebisacrylamide, 0.45 g of ammonium persulfate and water; in step d, the solid content of silicon carbide in the gel slurry is 45 wt %;

[0105] In step e, the phenolic resin solution contains 50 g of phenolic resin monomer.

[0106] Example 4

[0107] The method of Example 1 was adopted, except that in step a, the amount of acrylamide used was 60 g and the amount of bismethyl acrylamide used was 6 g.

[0108] Example 5

[0109] The method of Example 1 is adopted, except that in step a, the gel monomer used in the gel slurry is dimethyl acrylamide and the cross-linking agent is methylene bis acrylamide.

[0110] Example 6

[0111] a. A needle-punched embryo is obtained by acupuncture of the unit layers, wherein the density of the needle-punched embryo is 1.2 g / cm 3 The acupuncture density is 42 needles / cm 3 ;

[0112] b. Mix 2 g of ethylene glycol, 200 g of silicon carbide powder, 10 g of acrylamide, 1 g of methylenebisacrylamide, 0.25 g of ammonium persulfate and water to obtain a gel slurry;

[0113] c. Degassing the gel slurry in step b, immersing 600 g of the acupuncture embryo in step a into the degassing gel slurry, and performing vacuum treatment for 0.5 h to obtain the acupuncture embryo immersed in the gel slurry;

[0114] d. Taking out the needle-punched embryo body soaked in gel slurry for curing and drying to obtain a silicon carbide matrix, wherein the curing temperature is 60° C., the curing time is 4 h, the drying temperature is 100° C., the drying time is 3 h, and the solid content of silicon carbide in the gel slurry is 40 wt %;

[0115] e. Mix the silicon carbide substrate in step d with a phenolic resin solution having a concentration of 15 wt %, and perform a vacuum treatment for 0.5 h, and then perform a drying treatment. Place the dried silicon carbide substrate in an oven at 150° C. for curing for 2 h to obtain a cured embryo, wherein the drying temperature is 60° C., the drying time is 8 h, the phenolic resin solution contains 100 g of phenolic resin monomer, and the mass ratio of silicon carbide in the gel slurry to the phenolic resin monomer in the phenolic resin solution is 2:1;

[0116] f. placing the solidified embryo in step e in a carbonization furnace for carbonization treatment and removing burrs and processing heat dissipation holes to obtain a carbonized embryo, wherein the carbonization temperature is 1000° C. and the holding time is 2 h;

[0117] g. Liquid phase siliconizing the carbonized body in step f to obtain a carbon ceramic body, wherein the silicon source is silicon powder, the siliconizing temperature is 1700° C., and the heat treatment time is 2 h;

[0118] h. Mechanically process the disk surface and side surfaces of the carbon ceramic body in step g to obtain a carbon ceramic material.

[0119] Comparative Example 1

[0120] a. Mix 600 g of carbon fiber needle-punched embryo with a phenolic resin solution having a concentration of 40 wt %, and perform vacuum treatment for 0.5 h, and then perform drying treatment. Place the dried silicon carbide substrate in an oven at 150° C. for curing for 2 h to obtain a cured embryo, wherein the drying temperature is 60° C. and the drying time is 8 h;

[0121] b. placing the solidified embryo in step a in a carbonization furnace for carbonization treatment and removing burrs and processing heat dissipation holes to obtain a carbonized embryo, wherein the carbonization temperature is 1000° C. and the holding time is 2 h;

[0122] c. Liquid phase siliconizing the carbonized body in step b to obtain a carbon ceramic body, wherein the silicon source is silicon powder, the siliconizing temperature is 1700° C., and the heat treatment time is 2 h;

[0123] d. Mechanically process the disk surface and side surfaces of the carbon ceramic body in step c to obtain a carbon ceramic material.

[0124] Comparative Example 2

[0125] The method of Example 1 is adopted, except that the mass ratio of silicon carbide in the gel slurry to the phenolic resin monomer in the phenolic resin solution is 1:3, wherein the gel slurry contains 55g of silicon carbide and the phenolic resin solution contains 165g of phenolic resin monomer.

[0126] Comparative Example 3

[0127] The method of Example 1 is adopted, except that the mass ratio of silicon carbide in the gel slurry to the phenolic resin monomer in the phenolic resin solution is 8:1, wherein the gel slurry contains 195.5 g of silicon carbide and the phenolic resin solution contains 24.5 g of phenolic resin monomer.

[0128] Test Case

[0129] The carbon ceramic materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested in the following manner:

[0130] The flexural strength of the prepared product was measured by a universal testing machine (equipment model WDW-05), and the test standard was GB / T6569.

[0131] The compressive strength of the prepared product was measured by a universal testing machine (equipment model WDW-05), and the test standard was GB / T34559.

[0132] The density of the prepared product was measured by a porosity tester (equipment model YD-151C), and the test standard was GB / T25995-2010.

[0133] The free silicon size of the prepared product was measured by scanning electron microscopy (equipment model JEOL 7000F), the test standard was GB / T 16594-2008, and the average value of 30 groups of free silicon sizes was taken.

[0134] The average pore size was measured by an absorption resistance meter (equipment model HAD-DZK), and the test standard was GB / T1967-1996.

[0135] Table 1

[0136]

[0137]

[0138] According to the test results in Table 1, it can be seen that, compared with the comparative example, the carbon ceramic material provided by the present invention has a small pore diameter of the silicon carbide substrate obtained in the preparation process, and the finally obtained carbon ceramic material has small-sized free silicon and a small free silicon content, a dense material structure, high bending and compressive strength, and excellent mechanical strength and mechanical properties.

[0139] It can be seen from the test results of Examples 1, 2 and 6 that when the preparation method and processing conditions, the mass ratio of silicon carbide in the gel slurry and the phenolic resin monomer in the phenolic resin solution, and the concentration of the components in the gel slurry are within the specified range of the present disclosure, the effect and performance of the product prepared by the present invention can be further improved; from the test results of Examples 3 to 5, it can be seen that when the mass ratio of silicon carbide in the gel slurry and the phenolic resin monomer in the phenolic resin solution, the amount and type of components in the gel slurry, and the type of carbon fiber embryo are within the preferred range of the present disclosure, the free silicon size of the carbon ceramic material can be further reduced, and the flexural strength and compressive strength can be further improved.

[0140] From the test results of Comparative Examples 1 to 3, it can be seen that since no gel slurry is used in Comparative Example 1 to perform an in-situ curing process on the carbon fiber needle-punched embryo, as shown in Tables 1 and Figure 2It can be seen that large-area and large-size free silicon appears in the prepared carbon ceramic material, resulting in a significant decrease in the bending and compressive strength of the product, and the mechanical strength and performance are significantly worse than those of Examples 1 to 6; since the mass ratio of silicon carbide in the gel slurry and the phenolic resin monomer in the phenolic resin solution in Comparative Example 2 is not within the specified range of the present disclosure, the pore diameter of the silicon carbide matrix obtained by in-situ curing is significantly larger than that of Examples 1 to 6, and the size of free silicon in the obtained carbon ceramic material is significantly increased, resulting in lower bending and compressive strengths of the material, and poor mechanical strength and performance of the material; since the amount of silicon carbide added in Comparative Example 3 is too high, some pores in the gel skeleton are too small or closed pores are formed. During the siliconization treatment, the silicon liquid cannot penetrate into the pores that are too small or the silicon liquid is insufficiently penetrated, and the closed pores that cannot be entered, and finally there are holes in the product, which causes the mechanical strength and mechanical properties of the prepared carbon ceramic material to be significantly reduced.

[0141] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0142] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0143] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A carbon ceramic material, wherein: The carbon ceramic material comprises a matrix and free silicon dispersed in the matrix, wherein the matrix comprises carbon fibers and silicon carbide; Wherein, the size of free silicon in the substrate is less than 10 μm.

2. The carbon ceramic material according to claim 1, wherein: The size of free silicon in the substrate is 1-7 μm.

3. The carbon ceramic material according to claim 1, wherein: Based on the total mass of the matrix, the content of carbon fiber in the matrix is ​​40-60wt%, the content of silicon carbide is 20-50wt%, and the content of free silicon is 1-10wt%.

4. The carbon ceramic material according to claim 1, wherein: The density of the carbon ceramic material is 2.0-2.3 g / cm 3 .

5. The carbon ceramic material according to claim 1, wherein: The carbon ceramic material has a bending strength of 9 to 14 MPa and a compressive strength of 100 to 160 MPa.

6. A method for preparing a carbon ceramic material, wherein: The method includes: S1, mixing silicon carbide powder, dispersant, gel monomer, crosslinking agent, initiator and water to obtain gel slurry; S2, after mixing the carbon fiber embryo and the gel slurry, performing a first curing treatment and a first drying treatment to obtain a silicon carbide matrix; S3, mixing the silicon carbide substrate and the thermosetting resin solution and performing a second drying treatment, and then sequentially performing a second curing treatment, a carbonization treatment and liquid phase siliconization; Wherein, the mass ratio of silicon carbide in the gel slurry to the thermosetting resin monomer in the thermosetting resin solution is (1-5):

1.

7. The method according to claim 6, wherein: In step S2, the diameter of the pores of the silicon carbide substrate is less than 20 μm.

8. The method according to claim 6, wherein: Relative to 100 parts by weight of water, the content of silicon carbide powder in the gel slurry is 225-400 parts by weight, the content of dispersant is 2-4 parts by weight, the content of gel monomer is 10-40 parts by weight, the content of crosslinking agent is 1-4 parts by weight, and the content of initiator is 0.25-1 part by weight.

9. The method according to claim 6, wherein: The mass ratio of the carbon fiber embryo to the silicon carbide powder in the gel slurry is (1.5-3):

1.

10. The method according to claim 6, wherein: Based on the total mass of the gel slurry, the solid content of the silicon carbide is 45 to 80 wt %.

11. The method according to claim 6, wherein: The thermosetting resin solution comprises a thermosetting resin monomer and an organic solvent, wherein the thermosetting resin monomer is selected from one of phenolic resin, epoxy resin and furan resin; and the concentration of the thermosetting resin solution is 5 to 40 wt %.

12. The method according to claim 6, wherein: The dispersant is selected from one or more of ethylene glycol and tetramethylammonium hydroxide; The gel monomer is selected from one or more of acrylamide derivatives; The cross-linking agent is selected from one or more of methylenebisacrylamide, vinyl chloride and ethylene; The initiator is selected from one or more persulfates.

13. The method according to claim 6, wherein: In step S2, the carbon fiber embryo body includes a carbon fiber needle-punched embryo body; The density of the carbon fiber needle punched embryo is 1.0-1.2 g / cm 3 The acupuncture density is 40 to 45 needles / cm 3 .

14. The method according to claim 6, wherein: In step S2, the mixing is performed under reduced pressure conditions, and the reduced pressure conditions include: a processing time of 0.5 to 0.8 h and a relative vacuum degree of 0.095 MPa or more.

15. The method according to claim 6, wherein: In step S2, the conditions of the first curing treatment include: a curing temperature of 60 to 70°C and a heat preservation time of 3 to 4 hours.

16. The method according to claim 6, wherein: In step S2, the conditions of the first drying treatment include: a drying temperature of 100 to 120°C and a drying time of 2 to 3 hours.

17. The method according to claim 6, wherein: In step S3, the mixing is performed under reduced pressure conditions, and the reduced pressure conditions include: a processing time of 0.5 to 0.8 h and a relative vacuum degree of 0.095 MPa or more.

18. The method according to claim 6, wherein: In step S3, the conditions of the second drying treatment include: a drying temperature of 60 to 70° C. and a drying time of 8 to 10 hours.

19. The method according to claim 6, wherein: In step S3, the conditions of the second curing treatment include: a curing temperature of 120 to 150° C. and a heat preservation time of 3 to 4 hours.

20. The method according to claim 6, wherein: In step S3, the carbonization treatment conditions include: the carbonization temperature is 1000-1200° C., and the insulation time is 3-4 hours.

21. The method according to claim 6, wherein: In step S3, the reaction conditions of the liquid phase siliconization include: the silicon source is selected from silicon powder, the heat treatment temperature is 1600-1750° C., and the heat treatment time is 1-2 hours.

22. A carbon ceramic material prepared by the method according to any one of claims 6 to 21.

23. Use of the carbon ceramic material according to any one of claims 1 to 5 and 22 in a vehicle or an aircraft.